2022
DOI: 10.3390/foods11162523
|View full text |Cite
|
Sign up to set email alerts
|

Green Technology for Pork Loin Wet Curing—Unconventional Use of Cow and Soy Milk Treated with Non-Thermal Atmospheric Plasma

Abstract: This study was conducted to evaluate the possibility of using plasma-activated cow and soy milk powders as a substitute for sodium nitrite for wet curing of pork meat (m. longissimus thoracis et lumborum). Pork loin slices were cured for 4 d at refrigerate conditions in four brines: water + salt (NC group), water + salt + sodium nitrite (PC group), water + salt + plasma-activated cow milk powder (B1 group), and water + salt + plasma-activated soy milk powder (B2 group). Importantly, brines from groups PC, B1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…5 However, the plasma treatment effect on the allergens and antinutritional factors was not evaluated for whole soymilk. Though Marcinkowska-Lesiak et al 6 induced plasma activation in soymilk, the study focused only on meat curing and did not discuss the effect on soymilk's harmful components. Similarly, using DBD plasma eradicated TIs alone from soybean powder.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the plasma treatment effect on the allergens and antinutritional factors was not evaluated for whole soymilk. Though Marcinkowska-Lesiak et al 6 induced plasma activation in soymilk, the study focused only on meat curing and did not discuss the effect on soymilk's harmful components. Similarly, using DBD plasma eradicated TIs alone from soybean powder.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that the texture profile and colour properties of the muscle protein were improved significantly in hairtail fish treated with atmospheric CP (Koddy et al ., 2021). Pork cured with plasma‐activated cow and soy milk powders had significantly higher redness ( a *) and lower TBARS values, with little change in aroma characteristics (Marcinkowska‐Lesiak et al ., 2022b). Plasma treatment had a significant sterilisation effect on pork and also increased the brightness ( L *) value (Sammanee et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%